Esther against Joseph’s Backdrop: the theology and history of an intertextual relationship - Hornung, Gabriel F. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2024)
Intro -- Acknowledgements -- Contents -- 1 Introduction: Currents in Scroll and Intertextual Scholarship -- Part One: The Allusive Megillah and the Scholarly Attempts to Understand It -- 2 Textual Connections and Scholarly Histories -- 3 Other Intertextual Relationships and Esther and Joseph's Good Looks -- Part Two: Compositional and Structural Considerations -- 4 Esther's Compositional History and the Development of its Allusive Purpose -- 5 The Redactional Stages and Narrative Cohesiveness of MT Esther's Final Literary Form -- Part Three: The Theology of Esther and Contrast of Daniel -- 6 The Theological Implications of Esther's Relationship with Joseph -- 7 Daniel's Position in Joseph and Esther's Intertextual Chain -- 8 Conclusion: Esther's Intertextual Reflections and Theological Additions -- Bibliography -- Subject Index -- Index of Secondary Authors -- Index of Biblical Passages.